Analisis Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Umkm Minimarket Erick - Vivi Nila Sari; Dina Atikah; Crespo Arya Anggara; Fitriany; Habieb Bayu Wicaksono (CV. ITTC INDONESIA, 2024)
Minimarkets are one of the fastest growing types of retail businesses in Indonesia. Employee performance in minimarkets is an important factor in determining business success. Employee satisfaction and motivation have a significant impact on their performance. This study aims to analyze the effect of job satisfaction and motivation on employee performance in minimarkets. The research method used is quantitative with data collection techniques through questionnaires. The results of the study show that job satisfaction and motivation have a significant positive effect on employee performance in minimarkets. Job satisfaction has a stronger influence on employee performance than work motivation. The findings of this study have important implications for minimarket managers to improve employee satisfaction and motivation. Efforts that can be made include providing adequate wages and benefits, creating a conducive work environment, providing opportunities for employee development, and building good communication between superiors and employees.